Reversal of mecamylamine‐induced effects in healthy subjects by nicotine receptor agonists: Cognitive and (electro) physiological responses. (20th February 2018) - Alvarez‐Jimenez, Ricardo; Hart, Ellen P.; Prins, Samantha; de Kam, Marieke; van Gerven, Joop M.A.; Cohen, Adam F.; Groeneveld, Geert Jan
Abstract : Aims: Establishing a pharmacological challenge model could yield an important tool to understand the complex role of the nicotinic cholinergic system in cognition and to develop novel compounds acting on the nicotinic acetylcholine receptor. Methods: This randomized, double‐blind, double‐dummy, placebo‐controlled, four‐way crossover study examined the effects of the nicotinic antagonist mecamylamine on a battery of cognitive and neurophysiological test with coadministration of a placebo, nicotine or galantamine in order to reverse the cognitive impairment caused by mecamylamine. Results: Thirty‐three healthy subjects received a single oral dose of 30 mg of mecamylamine (or placebo) in combination with either 16 mg of oral galantamine or 21 mg of transdermal nicotine (or its double‐dummy). Mecamylamine 30 mg induced significant disturbances of cognitive functions. Attention and execution of visual (fine) motor tasks was decreased, short‐ and long‐term memory was impaired and the reaction velocity during the test was slower when compared to placebo. Mecamylamine 30 mg produced a decrease in posterior α and β power in the surface electroencephalogram, effects that were reversed by nicotine coadministration. Memory and motor coordination tests could be partially reversed by the coadministration of nicotine. Conclusions: Mecamylamine administration induced slowing of the electroencephalogram and produced decrease in performance of tests evaluating motor coordination, sustained attention and short‐ and long‐term memory. These effects could be partially reversed by the coadministration of nicotine, and to a lesser extent by galantamine.